A simple twist of fate - Asher, April (St. Martin's Griffin, 2025)
"At the bright-eyed age of eighteen, witch Harlow "Harry" Pierce attended her first Fates Festival Finding Ceremony certain the Blue Willow Wisp would lead her to her Fated match, her cougar shifter boyfriend, Jaxon Atwood. But Fate had other plans, guiding her best friend to him instead. With a broken heart, all her belongings, and a vow to never return, Harry did the only thing a heartsick witch could do. Run. Thirteen years later, she returns to her magical hometown - with her half-human, half-shifter goddaughter in tow - hoping that not only would the town work its magic on the troubled teenager, but that the local Alpha of the Rocky Mountain Pack could help Grace identify - and control - her fiery abilities. Jaxon Atwood was a shifter of few words and even less patience... until his mother retired as Alpha of the Rocky Mountain Pack and left the running of things to him. It's a headache he didn't need, and one that brought the witch who'd ripped his heart from his chest knocking on his door. Ever since the disappearance of the town's Fate Witch over a decade ago, Fates Haven's magic has been slowly going haywire. There hasn't been a Fated Match made in thirteen years, putting the town in serious jeopardy of losing its title of Highest Fated Mates Percentage in the World. But now, something is stirring in Fates Haven, Colorado, and it smells like the past, tastes like change, and looks like A SIMPLE TWIST OF FATE"--